ANALISIS DAMPAK KERUGIAN TINDAK PIDANA PENGELABUAN (PHISING) MELALUI SOSIAL MEDIA (ANALYSIS OF THE IMPACT OF LOSSES FROM PHISING THROUGH SOCIAL MEDIA) - Rini Fathonah; Firganefi Firganefi; Gunawan Jatmiko; Aisyah Muda Cemerlang; Diana Diana (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Purpose: To provide new information and knowledge to readers about the impact of losses from phising through social media Methodology/approach: The research methodology used in the writing of this article is the normative legal research method, which is conducted by studying, observing, and examining several theoretical aspects related to legal principles, concepts, views, legal doctrines, legal regulations, and legal systems pertinent to the research problem. Results/findings: Phishing is a technique where scammers try to make their victims provide personal information, such as passwords, credit card numbers, or other financial information, by impersonating a trusted entity through fake emails or fake websites. The main goal of phishing is to steal the target's identity or gain illegal access to someone's account. With the information possessed by the phishing perpetrator, they can carry out various types of fraud, such as identity theft, money laundering, or attacks on computers and network systems. Phishing can have very serious impacts on victims, such as financial loss, identity theft, loss of personal data, stress, trauma, damage to reputation, and operational disruption. Limitations: This paper raises the formulation of the problem, namely how the impact of losses from phising through social media. Contribution: The writing of this article is intended for law faculty students, particularly in the study of health law, and as a guide for law enforcement practitioners in understanding about the impact of losses from phising through social media.